Investigation of the food value chain of ready-to-eat chicken and the associated risk for staphylococcal food poisoning in Tshwane Metropole, South Africa - Oguttu, J.W.; McCrindle, C.M.E.; Makita, K.; Grace, Delia (Elsevier, 2014)
A mapping of the informal food value chain revealed that there are four possible value chains and that chicken spilled over from formal to informal markets. The prevalence of S. aureus in RTE chicken samples (44%; 90% CI: 36.1%-52.2%) was high. The mean S. aureus counts in the ready to eat chicken was 10 to the power of 3.6 (90%CI: 10 to the power of 3.3-10 to the power of 3.9), and the risk of purchasing chicken of unsatisfactory quality (>10 to the power of 3 cfu/g) was 32.9% (90%CI: 25.5%-40.4%). The probability of food poisoning due to consumption of RTE chicken contaminated with staphylococcal enterotoxin was estimated to be 1.3% (90% CI: 0%-2.7%). Sensitivity analysis showed that the probability of S. aureus having the enterotoxin gene was the most sensitive parameter for food poisoning. This was followed by S. aureus concentration in RTE chicken and lastly the prevalence of S. aureus in ready-to-eat chicken. This study demonstrates the existence of a strong link between formal and the informal market. In view of the low risk observed, the relevant authorities in Tshwane should continue to support the informal sale of RTE chicken. However, there is still a need for provision of hygiene training to reduce the concentration levels of S. aureus on the RTE chicken, and to promote the sale of safer affordable source of protein for the large urban poor population in South Africa. This will also help secure the opportunities for employment associated with the trade.